GENDER RELATIONS IN JAVANESE CULTURE: AN ANALYSIS OF QS. AL-NISĀ'/4: 1 AND 34 - Maula, Nabila An'imatul; Jabbar, Hanief Abdul (Takafu: Journal of Tafsir and Gender Perspective, 2025)
This study discusses gender relations in Javanese society through the analysis of QS. al-Nisa': 1 and 34. These verses are often referenced in shaping relationships between men and women, particularly in Javanese society, which is characterized by strong traditions and social norms. This study aims to examine how the interpretation of QS. al-Nisa' verses 1 and 34 is understood and applied within Javanese cultural concepts such as kanca wingking and sumur, dapur, kasur as well as how Qur'anic values interact with local traditions. This research employs a qualitative approach using textual analysis of Qur'anic exegesis and cultural observation methods. The findings reveal a dynamic interaction between Qur'anic interpretations and Javanese cultural values, where the exegesis of these verses is often adapted to align with the prevailing patriarchal system. Nevertheless, there are efforts to reinterpret these verses to foster more just and equitable gender relations. This study contributes to a deeper understanding of the relationship between sacred texts and local cultures while offering a new perspective on examining gender relations within diverse societal contexts.